Perinatal exposure to 4-hydroxy-4′-isopropoxydiphenylsulfone alters the adipogenesis in adult mice: A sex-specific study - Shengnan Zhang; Jiatong Shen; Kaini Hu; Yitong Zhou; Yumeng Wang; Xin Wang; Kashif Hayat; Mingrong Qian (Ecotoxicology and Environmental Safety)
4-hydroxy-4′-isopropoxydiphenylsulfone (BPSIP), a common alternative to bisphenol A (BPA), has been detected in breast milk and across placental barriers. However, the long-term impacts of perinatal exposure to BPSIP on adipogenesis and susceptibility to metabolic disorders later in life remain poorly understood. This study explored the effects of early-life BPSIP exposure on obesity and metabolic dysfunction in a diet-induced obesity model. Pregnant ICR mice were administered with BPSIP via oral gavage at doses of 0.02, 0.1, and 0.5 mg/kg body weight/day from gestational day 6 to postnatal day 21. After weaning, male and female offspring from control and high dose groups were fed either a normal diet (ND) or a high-fat diet (HFD) for 6 weeks. Results showed that perinatal BPSIP exposure significantly increased serum cholesterol levels, parametrial white adipose tissue (pWAT) weight, and body weight in female offspring, whereas males exhibited the opposite trend. Gene expression analyses revealed sex-specific alterations in adipogenesis, lipid metabolism, and endocrine function within pWAT, with these effects being more pronounced in HFD-fed BPSIP-exposed offspring. These findings demonstrate that perinatal exposure to BPSIP disrupts lipid metabolism in a sex-dependent manner, underscoring the potential long-term metabolic risks associated with BPSIP exposure during critical developmental periods.